Аналіз археозоологічного матеріалу з місця затонулого судна ХІІІ ст. біля поселення Новий Світ (Крим) - Вейбер, А.В. (Археологія, 2018)
Стаття присвячена визначенню й опису видового складу тварин пам’ятки кораблекрушіння середньовічного судна, що знаходиться біля поселення Новий Світ (Крим). Визначені кістки є харчовими відходами і доповнюють картину для реконструкції повсякденного життя на кораблі в добу Середньовіччя. The study is devoted to the analysis of the osteological materials which were discovered at the underwater archaeological site of a sunken mediaeval ship near the Novyi Svit settlement. The information on finds of ancient ceramic fragments near the coast of Novyi Svit is known since 1960. Since then, this archaeological site was robbed by the local divers and tourists. As a result, part of the collection was lost forever. The expedition of the Center of Underwater Archaeology, the Taras Shevchenko National University of Kyiv, started its work aiming in protection at a place of the shipwreck in 1996. A written source was also found in which the events of a shipwreck were described. According to this source, there was an armed conflict between the crews of ships from Genoa and Pisa, following which the Pisan ship was burned down and flooded with its cargo. A precise date of the shipwreck is known: 12 August 1276. It is confirmed by typological features of the materials found which are dated by the end of the 13th century. The purpose of current work was to study the animal bones remnants which were the kitchen waste of the crew. The whole osteological material was analyzed by the indexes of species structure, anatomical part, age and sex of animals, traces of anthropogenic origin, as well as of informative potential which such analysis can present. In this paper, problems of bones’ taphonomy and of interpretation the materials in archaeological and historical context of the shipwreck are discussed. All bones belong to domestic animals, including cows, pigs, goats /sheep and horses. The fragmentation degree indicates the method of cooking applied on the ship. The data of the cooking method is supplemented with findings of kitchen utensils in the form of pots and pans. Elements of the bovine skeleton, which contain horns and third phalanges (hoofs), indicate that animals were transported alive and slaughtered as needed. The presence of pig bones in the sample implies the ethnic composition of the crew team. Consumption of those animals was prohibited for Muslim and Jewish peoples of the Mediterranean. The presence of horse bones in the sample may indicate the Italian origin of the crew. Despite the fact that the sample is incomplete and represents only a part of the entire material of the site, it is rather informative. The study results allow interpreting the role of meat in food traditions of a mediaeval ship crew. Исследование посвящено анализу остеологического материала, который был найден на территории археологического памятника средневекового кораблекрушения вблизи поселка Новый Свет. Информация о нахождении фрагментов древней керамики вблизи берега поселка Новый Свет известна с 1960 г. С того времени археологический памятник грабился местными ныряльщиками и туристами, вследствие чего часть коллекции была навсегда утрачена. Начиная с 1996 г., на месте кораблекрушения начала работать экспедиция Центра подводной археологии Киевского Национального университета им. Тараса Шевченко с охранной целью. Также был найден письменный источник, в котором описаны события кораблекрушения. Согласно письменному источнику между экипажами кораблей Генуи и Пизы возник конфликт, вследствие которого пизанский корабль был сожжен и затоплен вместе со своим грузом. Известна точная дата кораблекрушения — 12 августа 1276 г. Она подтверждается типологическими характеристиками найденного материала, который датируется концом ХIII в. Цель работы заключалась в изучении костных останков животного происхождения, которые были кухонными отходами команды экипажа корабля. Весь остеологический материал был проанализирован по показателям видового состава, анатомической части, возраста и пола животного, следов антропогенного происхождения, а также информационного потенциала, который может нам дать такой анализ. В работе освещаются проблемы тафономии костей, проблемы интерпретации материала в археологическом и историческом контексте событий кораблекрушения.